PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PETANI PADI DI KECAMATAN LIMBOTO - Ahmad , A Laswin; Mokoginta, Meity M; Indrianti , Merita Ayu; Djibran, Moh Muchlis (Universitas Jambi, 2025)
Agricultural extension plays an important role in improvingfarmers' work. This study aims to analyze the role of agriculturalextension workers in increasing the work productivity of ricefarmers in Limboto District and evaluate the level of workproductivity of farmers in the area. The method used isquantitative with a descriptive analysis approach and a Likertscale. This study assesses the role of extension workers inguiding farmers regarding self-ability, time management, andmanagement of technical problems in agricultural activities. Theresults of the study showed that the role of agricultural extensionworkers in Limboto District was very effective in increasing thework productivity of farmers, with an average score of 4 in eachindicator tested. The research sample was carried out on 44farmers by taking until they started on farmers who had 2hectares of land. The data analysis method was carried out in aquantitative descriptive manner with interview and observationmethods. The results showed that the increase in workproductivity of rice farmers in Limboto District, based on theindicators tested, obtained positive results with an average valueof 4, which indicates a good category. The effectiveness of therole of agricultural extension workers in this sub-district can becategorized as effective, with the achievement of 79% of thetarget set for the extension role. However, farmers' labourproductivity is only 72%, which shows that although extensionis effective, external challenges such as cost constraints andaccess to modern agricultural technologies still hinderagricultural yields. And the last is The relationship between theeffectiveness of the role of agricultural extension workers and thework productivity of farmers in this sub-district showedsignificant results, with a correlation coefficient value of 0.179and a significance value of 0.002. This shows that the moreeffective the extension workers are in carrying out their roles, thehigher the productivity achieved by farmers.